Zgodovina raziskovanja plazme - Južnič, Stanislav (Vakuumist, 1998)
The article describes the discovery of pinch effect and the development of magnetohydrodynamics, a new field of scientific research that had to push hardto get its place in scientific world.
Keywords: fizika plazme; plazma; zgodovinski pregledi